Passive transfer of anti-HBc after intravenous immunoglobulin administration in patients with cancer: a retrospective chart review. Issue 10 (October 2018) - Lu, Huifang; Lok, Anna S; Warneke, Carla L; Ahmed, Sairah; Torres, Harrys A; Martinez, Fernando; Suarez-Almazor, Maria E; Foreman, Jessica T; Ferrajoli, Alessandra; Hwang, Jessica P
Summary: Background: Patients previously infected with hepatitis B virus (HBV; indicated by positivity for anti-HBc) can experience HBV reactivation during cancer chemotherapy. Intravenous immunoglobulin infusion, which is frequently used in supportive care, might facilitate passive transfer of anti-HBc. We aimed to estimate the probability of passive transfer of anti-HBc after intravenous immunoglobulin infusion in patients with cancer. Methods: We reviewed institutional databases to identify adult patients who received outpatient chemotherapy between Jan 1, 2004, and Dec 31, 2011, at the University of Texas MD Anderson Cancer Center, Houston, TX, USA. Eligible patients had received intravenous immunoglobulin therapy, had tested negative for both anti-HBc and HBsAg before infusion, and had been tested for anti-HBc after infusion. The primary endpoint was the proportion of patients who became positive for anti-HBc after intravenous immunoglobulin infusion. Findings: 950 of 18 874 patients who underwent chemotherapy within the study time frame received intravenous immunoglobulin, of whom 870 had been tested for anti-HBc before infusion. 199 patients who were negative for anti-HBc before receiving intravenous immunoglobulin were retested after infusion, of whom 29 (15% [95% CI 10–20]) became positive for anti-HBc. The probability of anti-HBc conversion at 1 week after intravenous immunoglobulin infusion was 34% (95% CI 22–48) and at 12 weeks was 4% (2–7). Interpretation: Conversion of patients from anti-HBc negativity to anti-HBc positivity was common after intravenous immunoglobulin administration. However, the probability of a positive test decreased with time since infusion. Positive anti-HBc tests done shortly after intravenous immunoglobulin infusion should be interpreted with caution because they might indicate passive transfer instead of true infection. Funding: None.